Theileria parva infection seroprevalence and associated risk factors in cattle in Machakos County, Kenya - Wesonga, F.D.; Gachohi, John M.; Kitala, P.M.; Gathuma, J.M.; Njenga, M.J. (Springer, 2015)
The principle objective of this study was to estimate the infection seroprevalence and identify risk factors associated with Theileria parva infection in cattle on smallholder farms in Machakos County, Kenya. A total of 127 farms were selected by a proportional allocation approach based on the number of farms in four divisions in the county previously selected by stratified random sampling method. Subsequently, a total sample of 421 individual animals was randomly selected from the farms. Information on animal and relevant individual farm management practices was gathered using a standardized questionnaire. Prevalence of serum antibodies was determined using the enzyme-linked immunosorbent assay (ELISA). Multivariable logistic models incorporating random effects at the farm level evaluated the association between the presence of T. parva antibodies and the identified risk variables. The overall estimation of T. parva antibodies in the county was 40.9 % (95 % confidence interval of 36.1, 45.7 %). Seroprevalence to T. parva was significantly associated with animal age, vector tick infestation in the animal, tick control frequency, and administrative division. Further analyses suggested a confounding relationship between administrative division and both breed and grazing system and the T. parva seropositivity. Random effects model yielded intra-farm correlation coefficient (ICC) of 0.18. The inclusion of farm random effect provided a substantially better fit than the standard logistic regression (P = 0.032). The results demonstrate substantial variability in the T. parva infection prevalence within all categories of the cattle population of Machakos County of Kenya, where East Coast fever is endemic.